Drought Frequency for Rabi Season at Dharwad and Bijapur - Ratnam, B P; Joshi, S N (Annals of Arid Zone, 2016)
The drought frequency for rabi season with reference to crop duration of two stations of dry climatic type of Kamataka was studied. Out of the 20 years (1954-1973) studied, Dharwad suffered 9 droughts in the long season and 8 in the short season. Bijapur suffered 10 droughts in the long season and 9 in the short season. Bijapur experienced droughts of high intensity as compared to Dharwad. Failure or low amounts of rainfall caused the drought.